The Effect of Live Yeast and Yeast Extracts on Growth Performance of Nursery Pigs Weaned from Sows Fed Diets with or without Yeast Additives - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joseph A. Loughmiller (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 340 weaned pigs (241 × 600, DNA; initially 11.2 lb BW) were used in a 45-d study to evaluate previous sow treatment (control vs. yeast additives) and nursery diets with or without added yeast-based pre- and probiotics (Phileo by Lesaffre, Milwaukee, WI) on growth performance. At placement in the nursery, pigs were housed by pen based on previous sow treatment and randomly assigned to 1 of 2 dietary treatments with 5 pigs per pen and 17 replications per treatment. Treatments were arranged in a 2 × 2 factorial with main effects of sow treatment (control vs. yeast-based pre- and probiotic diet; 0.10% ActiSaf Sc 47 HR+ and 0.025% SafMannan) and nursery treatment (control vs. yeast-based pre- and probiotic diet; 0.10% ActiSaf Sc 47 HR+, 0.05% SafMannan, and 0.05% NucleoSaf from d 0 to 7, then concentrations were lowered by 50% from d 7 to 24). All pigs were fed a common diet from d 24 to 45 post-weaning. Progeny from sows fed diets with yeast additives had increased (P<0.05) ADG, ADFI, and BW from d 0 to 24 and d 0 to 45. However, pigs that were fed yeast additives in the nursery had an overall (d 0 to 45) tendency for reduced ADG (P= 0.079) and lighter ending BW (P= 0.086). In conclusion, offspring from sows fed a live yeast and yeast additives had increased ADG, ADFI, and BW. However, feeding live yeast and yeast additives only in the nursery tended to reduce ADG and ending BW.
Keywords: nursery pigs; probiotic; yeast extract; yeast